PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Arie Afzal; Abdul Rohman (Diponegoro Journal of Accounting, 2012)
Optimization of corporate value is obtained, among others, by implementingfinancial management functions, in which a financial decision affects the others, whicheventually affects the corporate value. financial management closely relates to criticaldecisionsmaking taken by the firm. This research aimed to analyze the effect of investment,funding decisions and dividend policy on the manufacture firm value listed in theIndonesia Stock Exchange.Samples were collected from 25 manufacture firms listed in the Indonesia StockExchange for the period of 2007-2010. To be included into the study samples, the firm hadto fulfill the criterion required. This research applied an Ordinary Least Square (OLS) testto find out the effects of investment decisions, funding decisions, and dividend policy on thecorporate value.The study resulted in a positive and significant effect of the investment decisionsand funding decisions on the corporate value. The positive effect explained that the higherthe invesment and funding decisions, the higher the corporate value. Howover, dividendpolicy had a negative insignificant effect on the corporate value.